Dibenzo-18-crown-6-functionalized organic nanotubes for the synergistic adsorption of dyes and phenols from aqueous solutions. (December 2022) - Yang, Zujin; Wei, Caifeng; Chai, Yuxin; Zhang, Jianyong; Ji, Hongbing
Abstract: Toxic organic pollutants including dyes and phenols in effluent have not be treated efficiently by traditional wastewater methods. Herein, a novel nanotubular material was prepared successfully via supramolecular self-assembly of N, N ′, N ″-(3-methylpyridine) benzenetriamide (TMPTA) and further modified with dibenzo-18-crown-6 groups to obtain crown-ether-functionalized nanotubes (TMPTA-CE). The crown-ether-based TMPTA-CE shows a unique cavity structure, positively charged pyridinium groups and especially favorite crown ether-cation host-guest interactions. The crown-ether-based material as an adsorbent exhibits superior synergistic adsorption ability towards anionic dyes and phenols. The maximum adsorption capacities of MO, BPA and PNP for TMPTA-CE reached 802.23, 105.69 and 98.03 mg/g, respectively, with the removal efficiency of >99 %. The existence of K + ions can improve the adsorption capacities of BPA and PNP by about 28.14 % and 42.82 %, respectively. Notably, no significant change in adsorption efficiency was observed after 5 repeated adsorption-desorption cycles. Mechanism studies shows that synergistic effect of π-π interaction, electrostatic attraction and hydrogen-bond interaction played a significant role for the adsorption of anionic dyes and phenols. The results shows that the as-synthesized TMPTA-CE adsorbent with a simple, efficient and low-cost synthetic process has potential application in practical wastewater treatment. Graphical abstract: Unlabelled Image Highlights: Dibenzo-18-crown-6-functionalized nanotube (TMPTA-CE) was successfully synthesized. TMPTA-CE possessed positively charged pyridinium groups and crown ether-cation host-guest interactions. The maximum adsorption capacities of MO, BPA and PNP for TMPTA-CE reached 802.23, 105.69 and 98.03 mg/g, respectively, with the removal efficiency of >99 %. Synergistic effect of π-π interaction, electrostatic attraction and hydrogen-bond interaction played a crucial role in wastewater treatment.